Temperature-dependent broadening of spectral lineshapes and kinetics of luminescence centers in monoclinic gallium oxide nanowires - Chowdhury, Tasfia; Paul, Dholon Kumar; Rahaman, Md. Rabiur; Ton-That, Cuong; Rahman, M. Azizar (Journal of alloys and compounds, 2025)
The broadening of spectral lineshapes and kinetics of luminescence centers in highly crystalline monoclinic gallium oxide (β-Ga2O3) nanowires have been investigated through temperature-dependent cathodoluminescence (CL), transient photoluminescence (PL) as well as hybrid density functional theory (DFT). The results indicate that the holes are trapped onto two distinct sites of oxygen, forming two self-trap holes (STHs), namely STHO1 and STHO3, which are stable and optically active luminescence centers in β-Ga2O3 nanowires depending on temperature. The nanowires exhibit an ultraviolet luminescence (UVL) band at room temperature. The spectral lineshape of this UVL band shows an asymmetric broadening with decreasing temperature, which leads to the emergence of a new deep ultraviolet luminescence (DUVL) band below 220 K. These UVL and DUVL bands in β-Ga2O3 nanowires are attributed to STHO3 and STHO1 luminescence centers, which show similar thermal quenching behavior and possess short decay time constants of 7.11 and 5.25 ns, respectively. Hybrid DFT calculations and simulation of the UVL and DUVL bands using the Franck-Condon model reveal the vibronic coupling strength, zero phonon energies, and self-trapping energies of STHO1 and STHO3. •Holes are trapped in oxygen to form two types of self-trapped holes (STHs), namely STHo1 and STHo3 in β-Ga2O3.•Both the STHo1 and STHo3 are optically active luminescence centers in β-Ga2O3 nanowires.•The β-Ga2O3 nanowires show strong ultraviolet and deep ultraviolet emissions at 80 K attributed to STHo1 and STHo3.•Franck-Condon analysis reveals the thermodynamic transition and phonon coupling strengths of these luminescence centers.